Leadership and Management for Sustainable Development in Government Institutions and Local Self-Governance - Ioffe, Mykhailo; Biesova, Mariia Masyk; Chmil, Olena Berezovska; Voichuk, Alina; Antoniuk, Viktor (European Journal of Sustainable Development, 2025)
Achieving success in the orderly development of social relations involves ensuring effective regulatory influence based on public administration. The study aims to analyze the issues of modern peculiarities of management and leadership development in government and local self-government bodies. The article defines the motivational basis and specifics of forming leadership competences and skills. It is substantiated that the phenomenon of leadership is positioned as one of the essential components of the successful development of the public administration system. It has been found that the dynamics of social processes predetermine the formation of an innovative concept of activity of managers and leaders, who today must combine strict compliance with legal requirements and intensify the efficiency of management processes. It is substantiated that an effective manager should ensure the coordinated activities of structural units in the context of achieving common goals. It is determined that management and leadership in public administration are specified by the synergy of competence, skills and abilities of leaders and managers aimed at strengthening personal influence, developing strategic thinking and effective management decision-making, and rooting a strategy of continuous self-improvement. Examples of effective leadership and management in local sustainable development include the introduction of environmentally friendly technologies and reducing the carbon footprint, supporting social projects and improving living conditions in society, and implementing government policies on sustainable development and environmental protection. The article proves that management and leadership in government and local self-government bodies should be based on the principles of public administration, institutional support and mechanisms of vertical social mobility. It is established that institutional support requires updating in the context of ensuring the rule of law, improving the legislative framework, developing economic instruments of public administration, motivating managers to study and improve their skills, and implementing an effective internationally accepted anti-corruption policy. Keywords: management, public administration, leadership, authorities, local self-government bodies, human resources, sustainable development, corporate social responsibility, institutional stability.